If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -7 = 5x + 31 Reorder the terms: -7 + 11x = 5x + 31 Reorder the terms: -7 + 11x = 31 + 5x Solving -7 + 11x = 31 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 11x + -5x = 31 + 5x + -5x Combine like terms: 11x + -5x = 6x -7 + 6x = 31 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + 6x = 31 + 0 -7 + 6x = 31 Add '7' to each side of the equation. -7 + 7 + 6x = 31 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 31 + 7 6x = 31 + 7 Combine like terms: 31 + 7 = 38 6x = 38 Divide each side by '6'. x = 6.333333333 Simplifying x = 6.333333333
| 28=x^2+6x | | x^4-x^2=4x^2+36 | | 2x^2+2x-44=0 | | 5x-8=-76-7x | | 4(3x+2(2x+5))=32 | | 4x^2-15x+4=0 | | 1s+2t=-5 | | (y/-2)=-10 | | 4x+3y-50=180 | | 4x=5-2y | | 5t^2-5T-360=0 | | -8x-30=2x | | x^2+4-15x+10=2x-2 | | 20x^2+4x-24=0 | | (X^2+3)/(X+2) | | 2(x-3)+x(2-x)=2-x^2 | | 8/3x=16 | | (r/4)-3=7 | | 1/3m+1/6=4/9 | | 2x^2+13=73 | | f(x)=x^4-3x^2+4 | | 84*11/28*2/9 | | -(2x+4)=3x+5 | | 3(2)-5y=1 | | X^2+3/X+2 | | 8x^2-24x-144=0 | | x^2-6xy+8y^2=0 | | 3c*5e= | | 12a^2+15a^3= | | 1/4x+2=5 | | x/-3=12 | | 5-x=3x+4 |